Improved chemical exchange saturation transfer imaging with real‐time frequency drift correction. Issue 5 (30th January 2019) - Liu, Ruibin; Zhang, Hongxi; Niu, Weiming; Lai, Can; Ding, Qiuping; Chen, Weibo; Liang, Sayuan; Zhou, Jinyuan; Wu, Dan; Zhang, Yi
Abstract : Purpose: To investigate the effects of frequency drift on chemical exchange saturation transfer (CEST) imaging at 3T, and to propose a new sequence for correcting artifacts attributed to B0 drift in real time. Theory and Methods: A frequency‐stabilized CEST (FS‐CEST) imaging sequence was proposed by adding a frequency stabilization module to the conventional non‐frequency‐stabilized CEST (NFS‐CEST) sequence, which consisted of a small tip angle radiofrequency excitation pulse and readout of three non‐phase‐encoded k ‐space lines. Experiments were performed on an egg white phantom and 26 human subjects on a heavy‐duty clinical scanner, in order to compare the difference of FS‐CEST and NFS‐CEST sequences for generating the z‐spectrum, magnetization transfer ratio asymmetry (MTRasym ) spectrum, and amide proton transfer weighted (APTw) image. Results: The B0 drift in CEST imaging, if not corrected, would cause APTw images and MTRasym spectra from both the phantom and volunteers to be either significantly higher or lower than the true values, depending on the status of the scanner. The FS‐CEST sequence generated substantially more stable MTRasym spectra and APTw images than the conventional NFS‐CEST sequence. Quantitatively, the compartmental‐average APTw signals (mean ± standard deviation) from frontal white matter regions of all 26 human subjects were –0.32% ± 2.32% for the NFS‐CEST sequence and –0.14% ± 0.37% for the FS‐CEST sequence. Conclusions: The proposed FS‐CEST sequence provides an effective approach for B0 drift correction without additional scan time and should be adopted on heavy‐duty MRI scanners.